Assessing Systems for Hiring and Deploying Teachers in the Philippines - World Bank Group (World Bank, Washington, DC, 2016)
Over the last decade, research from many different countries has demonstrated the important role played by teachers in improving students' learning and increasing their competencies. Studies from countries as different as the US and Indonesia have shown the enormous benefits that follow from having adequate and effective teachers working in a country's schools. In Indonesia, a value-added analysis of student learning outcomes found that the more teachers know, the greater the improvements in the learning competencies of primary and junior secondary students. In the US, better teaching in elementary and secondary schools has been shown to increase students' college participation rates, raise their subsequent earnings, and improve other long-term outcomes.